Efektivitas Pelayanan E-Ticket terhadap Pengguna Jasa Penyeberangan Angkutan Bahan Bakar di Pelabuhan Kayangan - Yuniar Affandy; Salmi Yuniar Bahri; Agus Purnama (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to describe and analyze the effectiveness of E-Ticket services for users of fuel transportation crossing services at Kayangan port. The method used in this study is qualitative descriptive. Data collection techniques are carried out through interviews with informants who are considered to have the potential to provide information related to the problem being studied, also through observation and documentation. Effectiveness is the main element in achieving goals or targets that have been determined in any organization, activity, or program. It is called effective if the goals or targets are achieved according to what has been set. Efforts to evaluate the running of an organization can be done through the concept of effectiveness. In this case, effectiveness is the achievement of organizational goals through the efficient use of available resources, in terms of input, process, and output. This study describes the effectiveness of E-Ticket services for users of fuel transportation crossing services at Kayangan port which includes 3 focuses, namely the Source Approach, Process Approach, and Target Approach.